Tunable crystalline structure and electrical properties of (Pb, Sr)TiO3 films grown by liquid phase epitaxy. Issue 14 (17th March 2023) - Wollesen, Laura; Douissard, Paul-Antoine; Infante, Ingrid C.; Margueritat, Jeremie; Gautier, Brice; Martin, Thierry; Dujardin, Christophe
Abstract : Ferroelectric epitaxial films of Pb1− x Sr x TiO3 (PST) with nominal compositions of x = 0, 0.33, 0.39, and 0.43, supported by (100) SrTiO3 (STO) substrates, have been successfully grown by liquid phase epitaxy (LPE). Abstract : Ferroelectric epitaxial films of Pb1− x Sr x TiO3 (PST) with nominal compositions of x = 0, 0.33, 0.39, and 0.43, supported by (100) SrTiO3 (STO) substrates, have been successfully grown by liquid phase epitaxy (LPE). Energy dispersive X-ray measurements performed on selected films reveal an increase in the Sr-content for each nominal increase in the growth solution. Structural and spectroscopic investigations, from X-ray diffraction and Raman spectroscopy, unveil that all of the PST films possess a tetragonal structure at room temperature, and with increasing Sr-content, the tetragonality and Curie temperature decrease accordingly with values approaching those of reference bulk compound materials. These results confirm we achieved full control of the composition, structure, and transition temperature of the ferroelectric films, by adapting the nominal composition of the LPE growth solution, performing epitaxial growth while maintaining the bulk-like properties. Finally, using piezoresponse force microscopy, various nanoscale polar domain configurations for the PST epitaxial films were disclosed. This indicates that films having a higher Sr content can have polar domain configurations compatible with different a / c and c nanodomains. This work underlines the usefulness of the LPE method for controlling tetragonal ferroelectric PST film growth, in order to tune the nanoscale polarisation landscape in films having bulk-like structures and ferroelectric transition temperatures. This opens a path to new investigations fully exploiting the combined advantages of multiple nanoscale electrical boundary configurations within bulk-like ferroelectric films.